Pharmacokinetics of Oral Cannabinoid Δ8-Tetrahydrocannabivarin and Its Main Metabolites in Healthy Participants - Cristina Sempio; Jorge Campos-Palomino; Jelena Klawitter; Erica N. Peters; Laura MacNair; Mehdi Haghdoost; Marcel O. Bonn-Miller; Amy Harrison; Shanna Babalonis; Uwe Christians; Jost Klawitter (Pharmaceuticals)
Background: Tetrahydrocannabivarin (THCV) is a phytocannabinoid commonly found in cannabis with potential pharmacological properties; however, its post-acute pharmacokinetics (PK) in humans have not been studied yet. THCV has two isomers, Δ9- and Δ8-THCV, which seem to have different pharmacological properties. We investigated the PK of the Δ8-THCV isomer after oral administration as part of a two-phase, dose-ranging, placebo-controlled trial in healthy participants. Methods: Participants (n = 21) were enrolled in six study sessions and randomly received the following doses of a medium-chain triglyceride (MCT) oil oral formulation of Δ8-THCV: placebo, 12.5 mg, 25 mg, 50 mg, 100 mg, and 200 mg. Plasma samples from 15 participants were collected up to 8 h after administration and were analyzed by a validated two-dimensional high-performance liquid chromatography–tandem mass spectrometry assay. The trial was registered on clinicaltrials.gov (NCT05210634). Results: After oral administration, 11-nor-9-carboxy-Δ8-THCV (Δ8-THCV-COOH) was the main metabolite detected. The median time-to-maximum concentration (tmax) ranged 3.8–5.0 h across doses for Δ8-THCV and 4.6–5.3 h for Δ8-THCV-COOH. The maximum concentration (Cmax) and area under the concentration–time curve over the observation period (AUClast) appeared to be dose-linear. Median AUClast increased 2.3- to 4.8-fold and 1.7- to 2.9-fold for Δ8-THCV and Δ8-THCV-COOH, respectively, every two-fold increase in the dose. The isomers Δ9-THCV and Δ9-THCV-COOH were detected in plasma, despite being undetected in the formulated drug product analyzed by a third-party laboratory. Conclusions: For the first time, we report the pharmacokinetics of Δ8-THCV and its major metabolites after oral administration in humans. Δ8-THCV AUClast showed dose linearity but the observed possible conversion to the Δ9-THCV isomer should be further studied.